VARIASI KONSENTRASI ASAM SITRAT SEBAGAI SUMBER ASAM TERHADAP SIFAT FISIK TABLET EFFERVESCENT EKSTRAK KERING KULIT BUAH MANGGIS (Garcinia mangostana L) - inding gusmayadi; pramulani mulya lestari; erike trisnande (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Citric acid is an acid source in effervescent tablet it reacts rapidly, can increase dissolving time. In this research, extract was made into effervescent tablet. The research aimed at knowing increased concentration of citric acid as acid source can improve the physical characteristic of effervescent tablet. Pericarp mangosteen dry extracts macerated by water, and powder made by spray dryer. Dry extract was made into 5 formulas effervescent tablet with the different concentrations of citric acid, 15%, 20%, 25%, 30% and 35% as acid sources. The tablets were evaluated included organoleptic evaluation, weight uniformity, size uniformity, hardness, friability, and dissolving times. The result of dissolving time are 10,50±0,57 minutes, 4,52±1,04 minutes, 3,32±0,13 minutes, 3,13±0,14 minutes and 3,42±0,14 minutes. By one way ANOVA test dissolving time data showed differences each other 95% in signifigancies. It can be concluded that increasing of citric acid gave effect on dissolving time, and the citric acid with concentration of 35% can reduce dissolving time of the pericarp mangosteen (Garcinia mangostana L.) dry extract effervescent tablets.